2015
DOI: 10.1016/j.socec.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning on what? Heterogeneous contributions and conditional cooperation

Abstract: We experimentally investigate how different information about others' individual contributions affects people's willingness to cooperate in a one-shot linear public goods game. We find that when information about individual contributions is provided, contributions are generally higher than when only average information is available. This effect is particularly strong when others' individual contributions are relatively homogeneous. When both types of information are provided, this effect is moderated. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…On average, individuals tended to contribute less when there was more heterogeneity in peer contributions (linear mixed model with subject as random factor, P < 0.001; see Supplementary Information , section 3 for a detailed overview of statistical methods). This is in accordance with earlier studies 32 33 34 . In addition, we observe that in two of the three comparisons the variation in response contributions was higher in case of more heterogeneity in peer contributions (for averages 10 and 13.33, Brown-Forsythe test: P < 0.001; for average 6.67, Brown-Forsythe test: P = 0.733).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…On average, individuals tended to contribute less when there was more heterogeneity in peer contributions (linear mixed model with subject as random factor, P < 0.001; see Supplementary Information , section 3 for a detailed overview of statistical methods). This is in accordance with earlier studies 32 33 34 . In addition, we observe that in two of the three comparisons the variation in response contributions was higher in case of more heterogeneity in peer contributions (for averages 10 and 13.33, Brown-Forsythe test: P < 0.001; for average 6.67, Brown-Forsythe test: P = 0.733).…”
Section: Resultssupporting
confidence: 94%
“…One might expect that people take this variation in cooperation strategies into account when making decisions on their own degree of cooperation. In fact, some studies 32 33 34 have reported that, on average, individuals tend to reduce their contribution to a public good if the contributions of their peers are more heterogeneous. However, it is not clear how this effect arises.…”
mentioning
confidence: 99%
“…altruism | strategy method | inequity aversion | reciprocity | social preferences I t is an accepted paradigm that humans can be divided into fairminded cooperators that act for the good of the group and selfish "free riders" that exploit the altruism of others (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). This conclusion comes from the results of economic experiments, where people in small groups are given some money to play games with.…”
mentioning
confidence: 99%
“…First, in our experiment (see below) subjects were only provided with information about average but not individual behavior of others, which renders individual payoff comparisons difficult. Second, as shown by Hartig et al (2015), even if individuals are provided with information about individual contribution behavior, the majority of people who do react positively to others' contributions are indeed mainly guided by the average contribution of others (rather than, e.g., by the highest or the lowest contribution). A player i's objective function can then be written as…”
Section: The General Setup and Theoretical Considerationsmentioning
confidence: 99%